FEATURES OF MENSTRUAL AND GENERATIVE FUNCTION DISORDERS IN DEPRESSIVE DISORDERS OF ENDOGENOUS NATURE - Belov, O.O.; Kostyuk, A.L.; Andriichuk, V.M.; Kostyuk, I.Yu. (World of Medicine and Biology, 2020)
Menstrual and generative dysfunction in 104 women with depressive disorders was studied. Decreased generative function with a small number of pregnancies and births, decreased or no libido and sexual life; at the same time realization of generative function worsens with deepening of depression. Women with depressive disorders have a significant incidence of dysmenorrhea (83% in total), the prevalence of which also increases with the severity of depression. The most common disorders are opsomenorrhea (41%), amenorrhea (33%) and oligomenorrhea (20%). The prevalence of premenstrual syndrome among women with depression was 57%; it varies from 48% in mild depression to 90% in severe.